The Quality of Madrasa Education In The Digital Era - Kurniawan, Ade Rahmad; Sari, Putri Permata; Ayu, Sovia Mas (Universitas Islam Negeri Raden Intan Lampung, 2023)
Madrasa education in the era of computerization has gradually changed various aspects of life in the public arena. For this reason, various difficulties, benefits, and obstacles in the implementation of learning are a source for educators and other partners to play an effective role in understanding the vision and mission to be achieved in their respective schools. Instructive change has transformed disconnected training into online schooling. Distance is not a barrier to training. Advanced learning is web-based learning utilizing web information, known as on the web. This exploration strategy uses subjective examination with subjective enlightenment techniques through perception. This research explains how MTs Riydhol Jannah and West Lampung improve education quality management. The purpose of this research is to find out how the implementation of the program and the system used by Madrasa Tsanawiyah is different but has their own uniqueness and characteristics, as well as the uniqueness of the subjects studied. In general education institutions such as the Education System (KBM), Madrasa education emphasizes more on religious subjects. The learning methods are applied using an educational approach that supports the active role of students. The curriculum uses the 2013 Free Learning Curriculum (KMB) (K13) issued by the Ministry of Religious Affairs and the Ministry of Education and Culture. Because home education developed by Madrasa is adapted to the development and practices taught at MTs Riydhol Jannah West Lampung. Evaluation to determine and assess the results of the implementation of efforts to improve the quality of the madrasa using the CIIP evaluation approach model. The method of this research is qualitative by conducting interviews, and observations to find out how the implementation of the program in an effort to improve the quality of the madrasa in the third era at Madrasa Tsanawiyah Riydhol Jannah West Lampung, Indonesia